2016
DOI: 10.1093/mnras/stw2233
|View full text |Cite
|
Sign up to set email alerts
|

Lyα and C iii] emission inz= 7–9 Galaxies: accelerated reionization around luminous star-forming systems?

Abstract: We discuss new Keck/MOSFIRE spectroscopic observations of four luminous galaxies at z 7 − 9 selected to have intense rest-frame optical line emission by Roberts-Borsani et al. (2016). Previous spectroscopic follow-up has revealed Lyα emission in two of the four galaxies. Our new MOSFIRE observations confirm that Lyα is present in the entire sample. We detect Lyα emission in the galaxy COS-zs7-1, confirming its redshift as z Lyα = 7.154, and we detect Lyα in EGS-zs8-2 at z Lyα = 7.477, verifying a tentative de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
366
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 330 publications
(411 citation statements)
references
References 80 publications
39
366
6
Order By: Relevance
“…Pentericci et al (2016) reported velocity shifts of ∼100 km s −1 between [C II] and Lyα for their three most significant detections. For a higher-luminosity galaxy, Stark et al (2017) reported an offset between CIII] and Lyα of ∼340 km s −1 . Given the small velocity offset of RX J1347:1206 (and similar other low-luminosity galaxies), it seems that at z∼7, Lyα is much closer to systemic velocity than is the case for low-z LAEs at similar UV-continuum luminosities.…”
Section: Resultsmentioning
confidence: 99%
“…Pentericci et al (2016) reported velocity shifts of ∼100 km s −1 between [C II] and Lyα for their three most significant detections. For a higher-luminosity galaxy, Stark et al (2017) reported an offset between CIII] and Lyα of ∼340 km s −1 . Given the small velocity offset of RX J1347:1206 (and similar other low-luminosity galaxies), it seems that at z∼7, Lyα is much closer to systemic velocity than is the case for low-z LAEs at similar UV-continuum luminosities.…”
Section: Resultsmentioning
confidence: 99%
“…Velocity shifts between optical/UV lines, and in particular relative to Lyα, have been found and investigated by several authors (e.g. Pettini et al 2002;Shapley et al 2003;Gallerani et al 2016;Stark et al 2017;Williams et al 2014;Erb et al 2014). In the case of Lyα IGM absorption can cause the centroid of Lyα to be artificially redshifted (i.e.…”
Section: Spatial and Spectral Offsetsmentioning
confidence: 94%
“…At z 8 that wavelength range contains C III] 1907, 1909 ll Å. The resulting equivalent width would be in excess of ∼500 Å, physically unlikely (see e.g., Stark et al 2017 who found EW 22 0~Å for C III] at z 7 ). Even assuming that C III] is dominating the flux in the UltraVISTA H band, similar EW for CIV would be required to explain the flux in the K S band, together with a very red SED red-ward of K S to match the fluxes in the 3.6 μm and 4.5 μm bands.…”
Section: Appendix a Inconsistent Flux Measurements And Interlopersmentioning
confidence: 94%